2008
DOI: 10.1159/000189210
|View full text |Cite
|
Sign up to set email alerts
|

C-Flex® Technology: Effects on Breathing Parameters and Inspiratory Flow Limitation

Abstract: Background: Expiratory pressure relief continuous positive airway pressure (pressure relief CPAP, C-Flex®) is known to be as effective in the treatment of obstructive sleep apnea (OSA) as conventional CPAP while improving overall patients’ adherence. However, the effects of C-Flex on ventilation during sleep have not been studied yet. Objective: This study investigates the effects of pressure relief CPAP on respiratory parameters and possible inspiratory flow limitation with increased difference between inspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, in a prospective randomized study with 24 patients, our group demonstrated that there is no statistically significant difference regarding the occurrence of flow limitations with C-Flex compared to CPAP [33]. We also demonstrated that higher C-Flex gains were associated with a decrease in expiratory time in favor of the inspiratory duty cycle, while there was no significant change in tidal volume.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, in a prospective randomized study with 24 patients, our group demonstrated that there is no statistically significant difference regarding the occurrence of flow limitations with C-Flex compared to CPAP [33]. We also demonstrated that higher C-Flex gains were associated with a decrease in expiratory time in favor of the inspiratory duty cycle, while there was no significant change in tidal volume.…”
Section: Introductionmentioning
confidence: 71%
“…The available data might suggest an increase in the inspiratory work of breathing for increasing C-Flex gains, since a higher inspiratory duty cycle and higher inspiratory-to-expiratory time ratio are needed to achieve the same inspiratory tidal volume [34]. Such a change was demonstrated in case of flow limitations, which were not seen in any C-Flex setting [33]. Changes in duty cycle are predominant, while increases in breathing rate are much less pronounced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation